Caffeine therapy in preterm infants - Abdel-Hady, Hesham (World J Clin Pediatr, 2015)
Caffeine is the most commonly used medication for treatment of apnea of prematurity. Its effect has been well established in reducing the frequency of apnea, intermittent hypoxemia, and extubation failure in mechanically ventilated preterm infants. Evidence for additional short-term benefits on reducing the incidence of bronchopulmonary dysplasia and patent ductus arteriosus has also been suggested. Controversies exist among various neonatal intensive care units in terms of drug efficacy compared to other methylxanthines, dosage regimen, time of initiation, duration of therapy, drug safety and value of therapeutic drug monitoring. In the current review, we will summarize the available evidence for the best practice in using caffeine therapy in preterm infants.